MANAJEMEN OPERASI BERBASIS WEB - Faris Mahdi (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2002)
The explosion in the use of the Internet/Intranet and its accessibility to individuals, and enterprises has dramatically changed the way organizations conduct business with its customers and partners. The Internet/Intranet with inherent features like easy access, real-time information, and low cost, is a natural driver for business operations solution. Further, related to Internet/Intranet, the Web is very critical component. Web makes the application easy to use and provides an intuitive way for users to interact.Web offers tremendous time and cost savings for corporate operations. Web based operations management is operating businesses in the Internet world. It is about using the power of digital information to understand the needs and preferences of customers and partners, to customize products and services for them, and then deliver the products and services as quickly as possible. Automated services offer businesses the potential to increase revenues, lower costs, and establish and strengthen customers and partner relationships. To achieve these benefits, many enterprises engage in electronic commerce for business operations. In the future, Web will be common tool in any activities for both individual and enterprises.